Analisis Quality Control pada Produksi Karung Semen dengan Menggunakan Metode SQC (Statistical Quality Control) & RCA (Root Cause Analysis) di PT XYZ - Pangastuti, Ringgit; Safirin, Muhammad Tutuk (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT XYZ as a cement sack manufacturer still faces product defect issues that have the potential to reduce efficiency and quality. This study aims to analyze the level of defects, the stability of the production process, and identify the root causes of defects using Statistical Quality Control (SQC) and Root Cause Analysis (RCA) methods. The data analyzed came from the period January–June 2025 with a total production of 3,355,452 units and the number of defects was 32,025 units (0.95%). The results of the Pareto analysis showed that the keperet defect had the largest contribution of 43.55% (13,946 units), followed by the folded patch 11.98% and the oblique triangle 11.38%. The P control chart showed a CL value of 0.0061 with all points between the UCL and LCL, while the C control chart produced a C̄ of 5,338 which was still within the statistical control limits. The RCA analysis identified human, machine, material, method, and environmental factors as the main causes of defects. Improvements focused on SOP consistency, machine maintenance, and material control.